2022
DOI: 10.1177/03635465221120388
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Walking Biomechanics After Physical Therapist–Led Care or Hip Arthroscopy for Femoroacetabular Impingement Syndrome: A Secondary Analysis From a Randomized Controlled Trial

Abstract: Background: Femoroacetabular impingement syndrome is characterized by chondrolabral damage and hip pain. The specific biomechanics used by people with femoroacetabular impingement syndrome during daily activities may exacerbate their symptoms. Femoroacetabular impingement syndrome can be treated nonoperatively or surgically; however, differential treatment effects on walking biomechanics have not been examined. Purpose: To compare the 12-month effects of physical therapist–led care or arthroscopy on trunk, pel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Forty-eight RCTs were selected for inclusion. 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 Preferred Reporting Items for Systematic Reviews and Meta-Analyses flow sheet of study selection can be found in Figure 1 . Included RCTs were published in 21 journals from 2011 to 2023 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Forty-eight RCTs were selected for inclusion. 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 Preferred Reporting Items for Systematic Reviews and Meta-Analyses flow sheet of study selection can be found in Figure 1 . Included RCTs were published in 21 journals from 2011 to 2023 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…129 Another two studies investigated the effects of exercise programs on walking biomechanics. 130,131 Furthermore, one study examined overground running, 132 while another explored stair ambulation before and after hip osteochondroplasty and labral-chondral debridement. 133 In addition, two studies assessed jumping/landing activities, 127,134 and two additional studies evaluated the biomechanics of squatting.…”
Section: Hip Related Painmentioning
confidence: 99%